The bibliography of Appalachia more than 4,700 books, articles, monographs and dissertations, topically arranged and indexed - Burch, John R., 1968- (Contributions to southern Appalachian studies, 2009)
"This bibliography of books, articles, monographs, and dissertations features more than 4,700 entries, divided into twenty-four subject areas such as activism and protest; Appalachian studies; arts and crafts; community culture and folklife; education; environment; ethnicity, race and identity; health and medicine; media and stereotypes; recreation and tourism; religion; and women and gender. Two indexes conclude the bibliography"--Provided by publisher.